Protect / Paisley Hope. - Hope, Paisley (Sky Ridge hotshots., 2025)
I walk into the local bar with my hotshot crew, dirty and exhausted, only to slam into my biggest regret. The twin sister of my lost best friend and the one who got away, Violette Taylor. I haven't seen her in years, but I haven't forgotten her either. I used to be Rowan to her. Now, I'm just King, the guy who broke her heart, but not for the reasons she thinks. Violette, a nurse and single mom, is back in town for good, and working hard to avoid anyone who reminds her of the past, especially a career hotshot like me. But when I fall into her care after an injury lands me in her burn unit, it feels like maybe it's fate. I know something she doesn't - life rarely offers second chances. I need to protect those I love. So, if this is my chance to make things right, I'm taking it.